Synthesis of isotopically labeled CIS-(3aR)-(-)-2,3,3a,4,5,9b-hexahydro-3-(N-propyl)-1H-benz[e]indole-9-carboxamide, a 5-HT1A receptor agonist - Stolle, Wayne T.; Easter, John A.; Ackland, Mark J.; Haadsma-Svensson, Susanne R.; Lin, Chiu-Hong; Hsi, Richard S. P. (Journal of labelled compounds & radiopharmaceuticals, 1997)
The title compound is a potent and selective 5‐HT1A receptor agonist with clinical potentials for treating anxiety and depression. It has been labeled with stable and radioactive isotopes to support ADME studies in animals and human subjects. Its carboxamide group was labeled with C‐14, C‐13, or C‐13, N‐15, and O‐18. To provide a radioligand for investigating the receptor binding characteristics of the compound, we also labeled it with tritium in the N‐propyl group to obtain the high specific activity of 86.7 Ci/mmol. © 1997 John Wiley & Sons, Ltd.